2019
DOI: 10.18203/issn.2454-5929.ijohns20192700
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of otitis externa among patients attending Otorhinolaryngology Department at Muhimbili National Hospital, Tanzania

Abstract: <p class="abstract"><strong>Background:</strong> Otitis externa is among the otological diseases with significant impact on the quality of life of sufferers. Little is known in Sub Saharan countries despite being the focus of such disease. The study aimed to determine the prevalence and clinical characteristics of otitis externa at Muhimbili National Hospital, Tanzania’s largest tertiary hospital.</p><p class="abstract"><strong>Methods:</strong> This was a hospital bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In other African countries, Streptococci species showed higher rate of resistance (40%) to ceftriaxone [ 22 ]. However, a report in Tanzania indicated a resistance rate to ceftriaxone (4.4%), penicillin (38.3%) and amoxicillin/clavulanic acid (40.4%) [ 23 ]. The possible explanation for these discrepancies might be due to differences in the study population, methods used, geographical variations in disease burden, practice of antimicrobials use and presence, and implementation of national antimicrobials use policy.…”
Section: Discussionmentioning
confidence: 99%
“…In other African countries, Streptococci species showed higher rate of resistance (40%) to ceftriaxone [ 22 ]. However, a report in Tanzania indicated a resistance rate to ceftriaxone (4.4%), penicillin (38.3%) and amoxicillin/clavulanic acid (40.4%) [ 23 ]. The possible explanation for these discrepancies might be due to differences in the study population, methods used, geographical variations in disease burden, practice of antimicrobials use and presence, and implementation of national antimicrobials use policy.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 The prevalence was also noted to decrease after age 60 years similar to the finding in a study in Enugu, but differing from that of Abraham et al where age >65 years were found to be more affected. 22,25 In contrast some other researcher found the peak age to be in 7-12 years age group. 26 In the present study, chronic otitis externa was found to be the commonest form encountered.…”
Section: Discussionmentioning
confidence: 88%
“…19 In the present study, there was no statistical significant difference in distribution noted for sex, age and types of otitis externa similar to what was depicted in the study from Tanzania however; there was a statistically significant difference in the distribution of treatment duration and types of otitis. 25 Otitis externa therefore was found to be a common otologic condition seen in the ORL clinic and chronic type was the commonest form encountered in our environment.…”
Section: Discussionmentioning
confidence: 93%
“…Otitis eksterna merupakan sebuah inflamasi di telinga bagian luar yang meliputi aurikulum, meatus akustikus eskternus, atau bisa keduanya 1 . Inflamasi yang terjadi pada otitis eksterna bisa bersifat akut maupun kronis dan biasanya disebabkan oleh infeksi bakteri dan jamur 2. Faktor risiko yang memicu terjadinya inflamasi pada telinga luar ialah perubahan derajat keasaman (pH) di liang telinga yang biasanya normal atau asam.…”
Section: Pendahuluanunclassified